Erythrocytic enzymopathy in Uzbekistan - Bakhramov, S M; Ashrabhodzhaeva, K K (Likars'ka sprava, 2011)
Erythrocyte enzymes participate in the main interactions promoting utilization of glucose-glycolytic, pentosophosphate cycles and glutation system. In this report we study on erythrocyte G6PD deficiency which is the impairment related to the gender and expressed with development of acute drug-associated hemolytic anemia. Out of 13187 studied subjects 122 showed carrying of deficiency of erythrocyte G6PD activity, from them 98 (80.3%) subjects were male, and 24 (19.7%) female. As a whole, among the revealed in the population studies, and also verified in clinic of the persons with deficiency of erythrocyte G6PD there were marked different pathological phenotypes: hereditary nonspherecytary hemolytic anemia, acute drug-induced hemolytic anemia, asymptomatic gene carrying and, selected by us disease with few symptoms. As a whole, among the revealed in the population studies, and also verified in clinic of the persons with deficiency of erythrocyte G6PD there were marked different pathological phenotypes: hereditary nonspherecytary hemolytic anemia, acute drug-induced hemolytic anemia, asymptomatic gene carrying and, selected by us disease with few symptoms.